Lithium ion battery negative electrode and preparation method and application thereof
The modified aromatic polymer forms a cationic conductive polymer layer, which solves the problem of thermal runaway reaction of lithium-ion batteries, improves its thermal stability and safety performance, and maintains electrochemical performance, achieving low-cost safety performance promote.
Patent Information
- Application Number
- CN202411314188.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2025-01-10
AI Technical Summary
The thermal runaway reaction of lithium-ion batteries leads to safety accidents, and the prior art is difficult to effectively improve its thermal stability and safety performance.
Using modified aromatic polymer as the cationic conductive polymer layer, an artificial SEI film layer is formed, with high temperature resistance, flexibility, flame retardancy and high compatibility, significantly inhibiting the growth of lithium dendrites and coating it with the negative electrode. The layer works synergistically to improve the thermal stability and electrochemical performance of the battery.
It significantly improves the thermal stability and safety performance of lithium-ion batteries, maintains the stability of cationic conduction, combines physical isolation and high ionic conductivity, reduces costs and improves electrochemical performance.
Smart Images

Figure BDA0005051648560000021 
Figure BDA0005051648560000091 
Figure BDA0005051648560000111
Abstract
Description
Technical Field
[0001] The present invention relates to the field of new energy technology, and in particular to a lithium ion battery negative electrode and a preparation method and application thereof. Background Art
[0002] As the core component of pure electric new energy vehicles, the safety of lithium-ion batteries has become one of the key indicators restricting their further development. In addition to battery pack design defects, abuse during use and external environmental impact, the causes of lithium-ion battery safety accidents are mainly related to the composition, design and manufacturing process of single cells, among which the impact of battery composition on safety performance is particularly critical.
[0003] Research on the kinetic mechanism of thermal runaway reaction of lithium-ion batteries found that the whole process can be divided into three stages: (1) Internal thermal runaway stage of the battery. Due to heating, short circuit and other reasons, the internal temperature of the battery rises to about 100°C, the SEI film of the anode (negative electrode) begins to decompose, and the lithium embedded in the graphite reacts with the electrolyte, further pushing up the temperature inside the battery. (2) Battery swelling process. When the battery temperature rises to 200°C, the cathode (positive electrode) material decomposes, releasing a large amount of heat and gas. The lithium-embedded anode at 250-350°C begins to react with the electrolyte. (3) Overall thermal runaway of the battery. In this stage, as the internal pressure of the lithium-ion battery rises sharply, the outer packaging of the battery is broken, and the external oxygen, electrolyte vapor and combustible smoke / combustible smoke generated by various reactions react with each other, and then burn and catch fire, resulting in overall thermal runaway of the lithium-ion battery.
[0004] According to the above analysis, the negative electrode, as one of the four main materials of lithium-ion batteries, has an important impact on the comprehensive performance of lithium-ion batteries, especially in terms of safety performance. It is the first hurdle for thermal runaway of lithium-ion batteries. If the safety performance of the negative electrode of lithium-ion batteries can be improved, the overall safety performance of lithium-ion batteries can be improved to a certain extent. Summary of the invention
[0005] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention provides a lithium ion battery negative electrode, which can effectively improve its thermal stability, thereby improving the thermal safety of the lithium ion battery.
[0006] The present invention also provides a method for preparing the negative electrode of the lithium ion battery.
[0007] The present invention also provides application of the negative electrode of the lithium ion battery.
[0008] According to an embodiment of the first aspect of the present invention, there is provided a negative electrode for a lithium ion battery, the negative electrode for the lithium ion battery comprising a negative electrode current collector, a negative electrode coating and a cation conductive polymer layer arranged in a stacked manner;
[0009] The material of the cation conductive polymer layer is a modified aromatic polymer;
[0010] The modified aromatic polymer includes at least one of a sulfonamide-modified polymer and a sulfonated side-chain grafted polymer.
[0011] The negative electrode of the lithium ion battery according to the embodiment of the present invention has at least the following beneficial effects:
[0012] In the negative electrode of the lithium-ion battery provided by the present invention, the cation conductive polymer layer is equivalent to an artificial SEI film layer. Due to the selection of materials, the artificial SEI film layer has high high temperature resistance, flexibility, high flame retardancy, high voltage resistance, high compatibility with the electrode interface, and can significantly inhibit the growth of lithium dendrites. Specifically,
[0013] Unmodified aromatic polymers already have certain thermal stability, chemical stability, mechanical stability and antioxidant capacity; when coated on the surface of the negative electrode coating, they can be equivalent to an inert coating, maintaining stability and avoiding direct contact between the negative electrode coating and the electrolyte, which improves the performance of the negative electrode of the lithium-ion battery to a certain extent. However, due to its inert nature, it also increases the impedance of the negative electrode of the lithium-ion battery, so on the basis of improving safety performance, it loses electrochemical performance.
[0014] Compared with the unmodified aromatic polymer, the modified aromatic polymer used in the present invention further improves its thermal stability, maintains the stability of cation transfer to the polymer layer during the use of the negative electrode of the lithium ion battery, and forms a certain synergistic effect with the negative electrode coating. Specifically: the sulfonated side chain grafted polymer increases the side chain length and increases its thermodynamic stability; the hydrophilic sulfonic acid group is introduced on the side chain. Since the hydrophilic group is far away from the hydrophobic main chain, it can form an obvious "phase separation structure" at the nano level. The water absorbed by the sulfonic acid group is confined to the hydrophilic area, which reduces the influence of the hydrophilic group on the polymer main chain, so that the prepared sulfonated side chain grafted polymer can still maintain good dimensional stability at high temperatures. In the sulfonamide modified polymer, an amine group is introduced, which has unique properties in terms of conductivity, electrochemical properties, mechanical strength, chemical and electrochemical synthesis, etc., and can significantly improve its chemical stability, conductivity, processability and other performance. That is, the cation conductive polymer layer provided in the negative electrode of the lithium ion battery provided by the present invention has the functions of physical isolation, high stability and improved ion conductivity, and while improving the safety performance of the lithium ion battery, it also maintains / improves its electrochemical performance. Furthermore, the cation conductive polymer layer used in the present invention has the advantages of low cost and the like.
[0015] According to some embodiments of the present invention, the unmodified aromatic polymer includes at least one of polyaryletherketone, polysulfideethersulfone, polyetheretherketone, diazinidine polyethersulfoneketone, polyimide, polybenzimidazole, polyarylethersulfone, polyarylsulfone, sulfonated polyphenylene ether and polyphenylene polymer.
[0016] According to some embodiments of the present invention, the modified aromatic polymer is selected from at least one of sulfonamide-modified polyarylethersulfone and sulfonated side-chain grafted polyarylethersulfone.
[0017] That is, the unmodified aromatic polymer is preferably polyarylethersulfone, and its structural formula is as follows:
[0018]
[0019] According to some embodiments of the present invention, the synthesis method of the sulfonamide-modified polyarylethersulfone (PSF-NI for short) comprises the following steps:
[0020] A1. reacting a polyarylethersulfone and a sulfonyl compound to obtain a sulfonylated polyarylethersulfone;
[0021] A2. The sulfonylated polyarylethersulfone is reacted with an amide compound to obtain a sulfonamide-modified polyarylethersulfone.
[0022] The mechanism of the above reaction steps is as follows:
[0023] The polymer is prepared by using polyarylethersulfone as raw material, chlorosulfonic acid as sulfonyl compound and ammonia as amide compound through reactions such as chlorination and amidation.
[0024] In step A2, the amino group in the amide compound combines with the sulfonyl group in the sulfonylated polyarylethersulfone to form a sulfonamide group. Since the sulfonyl group connected to the nitrogen center has electron delocalization, the sulfonamide group exhibits a very high redox potential. At the same time, the NS bond is extremely difficult to cleave, so it has strong stability and is not easy to decompose at high temperatures. After being coated on the surface of the negative electrode of the lithium-ion battery, the thermal stability of the negative electrode of the lithium-ion battery is also increased.
[0025] The sulfonamide-modified polyarylethersulfone is a polymer with polyarylethersulfone as the main chain and benzenesulfonamide groups as the side chain.
[0026] According to some embodiments of the present invention, in step A1, the sulfonyl compound includes at least one of sulfonic anhydride, p-toluenesulfonyl chloride, and chlorosulfonic acid.
[0027] According to some embodiments of the present invention, in step A1, the molar ratio of the sulfonyl compound to the poly(arylethersulfone) is 1.2:1 to 1.5:1. This ratio is the molar ratio of the amide compound to the sulfone group in the poly(arylethersulfone).
[0028] According to some embodiments of the present invention, in step A1, the reaction temperature is 0-5° C. For example, it can be about 4° C. In actual production, an ice water bath can be used.
[0029] According to some embodiments of the present invention, in step A1, the reaction time is 2 to 4 hours, for example, about 2.5 hours, 3 hours or about 3.5 hours.
[0030] According to some embodiments of the present invention, in step A1, the reaction is carried out in a solvent, and the solvent used includes dichloromethane.
[0031] According to some embodiments of the present invention, step A1 further comprises solid-liquid separation, washing and drying after the reaction.
[0032] The solid-liquid separation method comprises mixing the system after the reaction with ice water and performing sedimentation.
[0033] The washing method includes water washing.
[0034] Methods of drying include freeze drying.
[0035] According to some embodiments of the present invention, in step A1, the reaction comprises the following steps:
[0036] A1a providing a dichloromethane solution of the polyarylethersulfone C;
[0037] Providing a dichloromethane solution D of the sulfonyl compound;
[0038] A1b. The dichloromethane solution C and the dichloromethane solution D are mixed for reaction.
[0039] According to some embodiments of the present invention, in step A1a, in the dichloromethane solution C, the mass volume ratio of the polyarylethersulfone to dichloromethane is 1 g:15-25 mL, for example, specifically about 1 g:20 mL.
[0040] According to some embodiments of the present invention, in step A1a, in the dichloromethane solution D, the volume ratio of the sulfonyl compound to the dichloromethane is 1:2-5, for example, about 1:3 or about 1:4.
[0041] According to some embodiments of the present invention, in step A2, the molar ratio of the amide compound to the sulfonated poly(arylethersulfone) is 1:1 to 1.2:1. This ratio is the molar ratio of the amide compound to the sulfonyl group in the sulfonated poly(arylethersulfone).
[0042] According to some embodiments of the present invention, in step A2, the amide compound includes at least one of ammonia, ethylamine and propylamine. In actual production, the amide compound is not strictly limited, and any organic amine that can react with sulfonate can be tried and similar effects can be obtained.
[0043] According to some embodiments of the present invention, in step A2, the reaction temperature is 15-40° C. For example, it can be about 20° C. or about 25° C. That is, in actual production, no additional temperature adjustment is required, and the operation can be performed at room temperature.
[0044] According to some embodiments of the present invention, in step A2, the reaction time is 4 to 6 hours, for example, about 4.5 hours, 5 hours or about 5.5 hours.
[0045] According to some embodiments of the present invention, step A2 further comprises washing and drying after the reaction is completed, wherein the washing method comprises water washing to remove byproducts such as ammonium chloride, and the drying method comprises drying.
[0046] According to some embodiments of the present invention, the peptide synthesis coupling agent includes at least one of N,N-dicarbonyl imidazole, N,N'-dicyclohexylcarbodiimide, diisopropylcarbodiimide, and 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride.
[0047] According to some embodiments of the present invention, the synthesis method of the sulfonated side-chain grafted polyarylethersulfone (PSF-SA for short) comprises the following steps:
[0048] D1. reacting the polyarylethersulfone with an acyl chloride compound to obtain an acylated polyarylethersulfone;
[0049] D2. reacting the acylated polyarylethersulfone and trisodium 8-hydroxy-1,3,6-pyrenetrisulfonate (HPTS) in the presence of an acid-binding agent and a catalyst.
[0050] According to some embodiments of the present invention, in step D1, the acyl chloride compound includes at least one of chlorobutyryl chloride, acetyl chloride, benzoyl chloride, butyryl chloride and propionyl chloride.
[0051] According to some embodiments of the present invention, in step D1, the molar ratio of the acyl chloride compound to the poly(arylethersulfone) is 1.1:1 to 1.3:1. This ratio is the molar ratio of the acyl chloride compound to the sulfone group in the poly(arylethersulfone).
[0052] When the acyl chloride compound is selected from chlorobutyryl chloride, in step D1, the mass volume ratio of the polyarylethersulfone to the chlorobutyryl chloride is 1 g:0.5-1 mL, for example, about 1 g:0.6 mL, or about 1 g:0.7 mL.
[0053] According to some embodiments of the present invention, in step D1, the reaction process comprises the following steps:
[0054] D1a. Providing a dichloromethane solution A comprising the polyarylethersulfone;
[0055] Providing a dichloromethane solution B including the acyl chloride compound;
[0056] D1b. The two solutions of step D1a are mixed and reacted.
[0057] According to some embodiments of the present invention, in step D1a, in the dichloromethane solution A, the mass volume ratio of the polyarylethersulfone to dichloromethane is 1 g:8-12 mL, for example, about 1 g:10 mL.
[0058] According to some embodiments of the present invention, in step D1a, the dichloromethane solution A further comprises aluminum chloride. The molar volume ratio of the aluminum chloride to dichloromethane is 0.2-0.3 mmol:1 mL. For example, it can be about 0.25 mmol:1 mL. The aluminum chloride acts as a catalyst.
[0059] According to some embodiments of the present invention, in step D1a, in the dichloromethane solution B, the volume ratio of the acyl chloride compound to dichloromethane is 1 to 2:10, for example, about 1.1:10, 1.2:10, 1.5:10 or about 1.8:10.
[0060] According to some embodiments of the present invention, in step D1a, the acyl chloride compound includes at least one of chlorobutyryl chloride, acetyl chloride, benzoyl chloride, butyryl chloride and propionyl chloride.
[0061] According to some embodiments of the present invention, in step D1b, the reaction temperature is 40-60°C, for example, about 50°C.
[0062] According to some embodiments of the present invention, in step D1b, the reaction time is 10 to 15 hours, for example, about 12 hours or about 13 hours.
[0063] According to some embodiments of the present invention, step D1 further includes removing the catalyst, alcohol precipitation, washing and drying in sequence after the reaction.
[0064] The operation of removing the catalyst includes mixing hydrochloric acid with the system after the reaction in step D1. The concentration of the hydrochloric acid is 0.5-1.5 mol / L, for example, it can be about 1 mol / L. The volume ratio of the hydrochloric acid to the mass ratio of the polyarylethersulfone is 0.1-0.15 mL: 1 g. For example, it can be about 0.125 mL: 1 g.
[0065] The alcohol precipitation method comprises mixing anhydrous ethanol with the system obtained after the reaction in step D1, wherein the volume ratio of anhydrous ethanol to the system obtained after the reaction in step D1 is 3.5 to 4.5:1, for example, specifically about 4:1.
[0066] The drying method includes vacuum drying, thereby further removing the residual solvent.
[0067] According to some embodiments of the present invention, in step D2, the molar ratio of the acylated polyarylethersulfone to trisodium 8-hydroxy-1,3,6-pyrenetrisulfonate (CAS: 6358-69-6) is 1 to 1.2:1. For example, it can be about 1.1:1.
[0068] According to some embodiments of the present invention, in step D2, the acid binding agent includes at least one of sodium carbonate, sodium bicarbonate, sodium hydroxide and triethylamine.
[0069] According to some embodiments of the present invention, in step D2, the mass / amount ratio of the acylated polyarylethersulfone to the acid binding agent is 1 g:9-10 mmol, for example, about 1 g:9.5 mmol.
[0070] According to some embodiments of the present invention, in step D2, the catalyst includes at least one of potassium iodide, sodium iodide and tetrabutylammonium iodide.
[0071] According to some embodiments of the present invention, in step D2, the mass ratio of the acylated poly(arylethersulfone) to the catalyst is 1:3-4, for example, about 1:3.5.
[0072] According to some embodiments of the present invention, in step D2, the reaction is carried out in a solvent. The mass volume ratio of the acylated polyarylethersulfone to the solvent is 1g:40-60mL. For example, it can be about 1g:45mL, 1g:50mL or about 1g:55mL. The types of solvents used include at least one of N,N-dimethylformamide, 1-methyl-2-pyrrolidone, dichloromethane and dimethyl sulfoxide. The above solvents have a high solubility for the acylated polyarylethersulfone and a high boiling point, so they can be used as stable solvents at the reaction temperature required in step D2.
[0073] According to some embodiments of the present invention, in step D2, the reaction temperature is 100-120°C, for example, about 105°C, 110°C or about 115°C.
[0074] According to some embodiments of the present invention, in step D2, the reaction time is 25 to 35 hours, for example, about 28 hours, 30 hours or about 32 hours.
[0075] According to some embodiments of the present invention, step D2 comprises the following steps:
[0076] After the acylated polyarylethersulfone is dissolved in the solvent, the acid-binding agent, the catalyst and 8-hydroxy-1,3,6-pyrenetrisulfonic acid trisodium are added in sequence for reaction. Thus, after the acylated polyarylethersulfone is dissolved, it is convenient to fully contact with other reagents. The order of adding the acid-binding agent can timely neutralize the acidic by-products, significantly avoiding the interference or damage of the acidic by-products to the reaction; potassium iodide, as a catalyst, should be added before another reactant 8-hydroxy-1,3,6-pyrenetrisulfonic acid trisodium to give full play to the catalytic effect. 8-hydroxy-1,3,6-pyrenetrisulfonic acid trisodium is a sensitive fluorescent dye, and it is added in the last stage to avoid unnecessary interference and degradation, and at the same time, ensure that it can fully react with the acylated polyarylethersulfone at a higher concentration.
[0077] Under the above-mentioned order of adding materials, it can ensure that each reagent can work under the best conditions, improve the reaction efficiency and product yield; at the same time, the occurrence of side reactions is avoided or reduced as much as possible, ensuring the smooth progress of the main reaction. In addition, the purity of the product is significantly improved.
[0078] According to some embodiments of the present invention, step D2 further includes sequentially performing alcohol precipitation and drying after the reaction. The alcohol used for the alcohol precipitation is ethanol; the volume of the alcohol used and the mass ratio of the acylated polyarylethersulfone used in step D2 are 110-130mL:1g. For example, it can be about 120mL:1g. The drying method used in this step includes vacuum drying.
[0079] According to some embodiments of the present invention, in the process of synthesizing the modified aromatic polymer, the polyarylethersulfone used is purchased from Ningbo Deqi Special Plastic Co., Ltd., referred to as PSF, model P-1700. In actual production, the model and the purchasing company are not strictly limited, as long as they can meet the specific thermal stability, mechanical stability and cation conductivity rate.
[0080] According to some embodiments of the present invention, the thickness of the cation-conducting polymer layer is 2.5-10 μm, for example, about 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm or about 10 μm.
[0081] According to some embodiments of the present invention, the negative electrode coating and the cation conductive polymer layer are disposed on one side surface of the negative electrode current collector. Specifically, the negative electrode of the lithium ion battery is a negative electrode current collector, a negative electrode coating and a cation conductive polymer layer stacked together.
[0082] According to some embodiments of the present invention, the negative electrode of the lithium ion battery is a cation conductive polymer layer, a negative electrode coating, a negative electrode current collector, a negative electrode coating and a cation conductive polymer layer which are stacked.
[0083] According to some embodiments of the present invention, the negative electrode of the lithium ion battery comprises a negative electrode coating, a negative electrode current collector, a negative electrode coating and a cation conductive polymer layer which are stacked.
[0084] According to some embodiments of the present invention, the negative electrode current collector includes copper foil.
[0085] According to some embodiments of the present invention, the raw materials for preparing the negative electrode coating include negative electrode materials, negative electrode conductive agents, negative electrode binders and thickeners.
[0086] The negative electrode material includes at least one of a silicon-based material and a carbon-based material; the silicon-based material includes at least one of elemental silicon, silicon-oxygen material and silicon-carbon material; the carbon-based material includes at least one of artificial graphite and natural graphite.
[0087] The negative electrode conductive agent includes at least one of acetylene black, carbon nanotubes and graphene.
[0088] The negative electrode binder includes SBR.
[0089] The thickener includes CMC.
[0090] The mass ratio of the negative electrode material, the negative electrode conductive agent, the negative electrode binder and the thickener is 190-200:1:1-2:1-2.
[0091] According to an embodiment of the second aspect of the present invention, a method for preparing a negative electrode of a lithium ion battery is provided, the preparation method comprising the following steps:
[0092] S1. Providing a cation conductive polymer layer slurry comprising the modified aromatic polymer, and a component in which the negative electrode current collector and the negative electrode coating are stacked;
[0093] S2. Coating the cation conductive polymer layer slurry on the surface of the component on the negative electrode coating side.
[0094] Since the preparation method adopts all the technical solutions of the lithium ion battery negative electrode of the above embodiment, it at least has all the beneficial effects brought by the technical solutions of the above embodiment.
[0095] Furthermore, the preparation method adopted in the present invention is simple to operate, and the raw materials for preparation are widely available and inexpensive, and is expected to be widely promoted in the industry.
[0096] According to some embodiments of the present invention, in step S1, the raw materials for preparing the cation conductive polymer layer slurry include the modified aromatic polymer and a solvent.
[0097] The mass ratio of the modified aromatic polymer to the solvent is 0.08 to 0.1:2. For example, it can be about 0.09:1. Within this range, the cation conductive polymer layer slurry has a suitable concentration and viscosity, so it is easy to form a film with uniform thickness and excellent leveling properties.
[0098] The solvent includes at least one of an alcohol solvent and a ketone solvent.
[0099] According to some embodiments of the present invention, the alcohol solvent includes at least one of methanol, ethanol and isopropanol.
[0100] According to some embodiments of the present invention, the ketone solvent includes at least one of acetone and butanone.
[0101] According to some embodiments of the present invention, the solvent is a mixture of the alcohol solvent and the ketone solvent in a volume ratio of 1:0.8 to 1.2. The specific volume ratio may be about 1:1.
[0102] According to an embodiment of the third aspect of the present invention, there is provided a lithium ion battery, the lithium ion battery comprising a battery cell, the battery cell comprising a positive electrode, a negative electrode and a separator disposed between the positive electrode and the negative electrode;
[0103] The negative electrode is the negative electrode of the lithium ion battery.
[0104] Since the lithium-ion battery adopts all the technical solutions of the lithium-ion battery negative electrode of the above embodiment, it at least has all the beneficial effects brought by the technical solutions of the above embodiment.
[0105] According to some embodiments of the present invention, the positive electrode comprises a positive electrode current collector and a positive electrode coating arranged in a stacked manner.
[0106] The positive electrode coating is disposed on one side or both sides of the positive electrode current collector.
[0107] The positive electrode current collector includes aluminum foil.
[0108] The raw materials for preparing the positive electrode coating include positive electrode material, positive electrode conductor and positive electrode binder.
[0109] The positive electrode material includes at least one of a polyanion material, a layered material and a spinel material.
[0110] The polyanion material includes at least one of lithium iron phosphate, lithium manganese phosphate, and lithium manganese iron phosphate.
[0111] The general formula of the layered material is LiMO2, wherein M includes at least one of nickel, cobalt, and manganese, for example, it may be at least one of lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide, and lithium nickel cobalt manganese oxide.
[0112] In the layered material, M also includes a doping element; the doping element includes at least one of aluminum, zirconium, magnesium, titanium, boron, and fluorine.
[0113] The spinel material includes lithium manganate (spinel phase).
[0114] The positive electrode conductive agent includes at least one of acetylene black, graphene and carbon nanotubes.
[0115] The positive electrode binder includes PVDF.
[0116] The mass ratio of the positive electrode material, the positive electrode conductor and the positive electrode binder is 120-125:1-2:1.
[0117] According to some embodiments of the present invention, the material of the diaphragm includes at least one of polyethylene and polypropylene.
[0118] According to some embodiments of the present invention, the lithium-ion battery further includes an electrolyte, and the electrolyte infiltrates the battery core.
[0119] According to some embodiments of the present invention, the raw materials for preparing the electrolyte include lithium salt and non-aqueous organic solvent. The mass ratio of lithium salt and non-aqueous organic solvent is 1:10-15. For example, it can be about 1:11, 1:12, 1:13 or about 1:14. The non-aqueous organic solvent includes at least one of carbonate and carboxylate. For example, it can be ethylene carbonate (EC), diethyl carbonate (DEC), propylene carbonate (PC), propyl propionate (PP) and vinylene carbonate (VC) mixed in a mass ratio of 6-7:6-7:3-4:7-8:1.
[0120] According to some embodiments of the present invention, the lithium-ion battery further comprises a battery case, wherein the battery case accommodates the battery cell.
[0121] It should be noted that the composition of the positive electrode, separator, electrolyte, and even the negative electrode coating in the lithium-ion battery can be adjusted according to actual conditions in actual production, and the present invention does not impose strict restrictions.
[0122] According to an embodiment of the fourth aspect of the present invention, there is provided an application of the lithium-ion battery in the field of power batteries, energy storage batteries and 3C small household appliances.
[0123] Since the application adopts all the technical solutions of the lithium-ion battery of the above embodiment, it at least has all the beneficial effects brought by the technical solutions of the above embodiment.
[0124] If there is no special explanation, the actual meaning of “about” in the present invention is that the error is allowed to be within the range of ±2%, for example, about 100 is actually 100±2%×100.
[0125] Unless otherwise specified, “between” in the present invention includes the number itself, for example, “between 2 and 3” includes the endpoint values 2 and 3.
[0126] Other features and advantages of the present invention will be set forth in the description which follows, and in part will be apparent from the description, or may be learned by practice of the present invention. DETAILED DESCRIPTION
[0127] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.
[0128] In the description of the present invention, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.
[0129] If there is no special explanation, the polymer sources used in the specific implementation method are as follows:
[0130] The Nafion 115 used in Comparative Examples 2 to 3 was purchased from Chemours, USA, and had a light yellow crumb appearance; the structural formula is as follows:
[0131]
[0132] The PSF (unmodified polyarylethersulfone) used in Comparative Examples 4 to 5 was purchased from Ningbo Deqi Special Plastics Co., Ltd., model P-1700;
[0133] The synthesis steps of PSF-SA (sulfonated side chain grafted polyarylethersulfone) used in Examples 1 to 6 are as follows:
[0134] D1a. In a four-necked flask containing dichloromethane (20.0 mL), dry PSF (2.0 g, same as PSF used in Comparative Examples 4 to 5) was added, and AlCl3 (4.50 mmol) (dichloromethane solution A) was added after dissolution;
[0135] Prepare a mixture of 1.14 mL of chlorobutyryl chloride (CAS: 7623-11-2) and 10.00 mL of dichloromethane (dichloromethane solution B);
[0136] D1b. Add dichloromethane solution B dropwise to dichloromethane solution A; react at 50°C for 12h;
[0137] After the reaction, the mixed solution was treated with 0.25 mL of hydrochloric acid (1 mol / L) to remove the catalyst, and the target product was precipitated with anhydrous ethanol (120.00 mL), and the target product was washed and dried to obtain the acylated polyarylethersulfone. The drying method includes vacuum drying.
[0138] D2. Use 50.00 mL of dimethyl sulfoxide to dissolve 1.00 g of acylated poly(arylethersulfone). After dissolution, add 9.50 mmol of sodium carbonate acid binder, 3.80 g of potassium chloride catalyst and 3.80 g of trisodium 8-hydroxy-1,3,6-pyrenetrisulfonate. React at 110 °C for 30 h. The mixed solution is precipitated with 120 mL of anhydrous ethanol and vacuum dried to obtain PSF-SA with increased side chain length.
[0139] The synthesis steps of PSF-NI (sulfonamide-modified polyarylethersulfone) used in Examples 7 to 12 are as follows:
[0140] A1. In a 50mL three-necked flask, add 20mL of dichloromethane, then stir and add 1g of polyarylethersulfone (PSF same as comparative examples 4-5) powder, after dissolving, slowly drop 3mL of chlorosulfonic acid (CAS: 7790-94-5) dissolved in 10mL of dichloromethane, and react in an ice water bath (about 0°C) for 3h; after the reaction is completed, pour the reaction product into ice water, precipitate, wash thoroughly with deionized water, and freeze-dry to obtain polyarylethersulfone sulfonyl chloride.
[0141] A2. The poly(aryl ether sulfone) sulfonyl chloride obtained in step 1 was put into a 50 mL three-necked flask, and ammonia gas (the amount used was 1.1 times the amount of poly(aryl ether sulfone) sulfonyl chloride) was introduced at room temperature. After reacting for 5 hours, the ammonia gas was fully volatilized, and the solid product obtained by the reaction was taken out, washed with water to remove ammonium chloride, and dried to obtain the sulfonamide-modified poly(aryl ether sulfone).
[0142] Example 1
[0143] In this example, a lithium-ion battery negative electrode is prepared, and the specific steps are as follows:
[0144] S1. The negative electrode material, conductive agent acetylene black, binder styrene butadiene rubber (SBR), and thickener sodium carboxymethyl cellulose (CMC) are fully stirred and mixed in a deionized water solvent system at a mass ratio of 98.1:0.5:0.7:0.7, and then coated on a Cu foil (negative electrode collector). After drying, rolling, and slitting, an intermediate component is obtained, which includes a superimposed negative electrode coating, a negative electrode collector, and a negative electrode coating.
[0145] The polymers listed in Table 1 are placed in a container with methanol and acetone at a mass ratio of 0.08:1:1, dissolved and stirred; the dissolving temperature is room temperature, and the stirring speed is 300-450r / min; after being fully mixed, a cation conductive polymer layer slurry is prepared;
[0146] S2. Apply the cation conductive polymer layer slurry obtained in step S1 on the surface of the negative electrode coating; the dry film thickness of the coating, single-sided coating or double-sided coating are all as shown in Table 1.
[0147] Examples 1 to 12 and Comparative Examples 1 to 5 respectively prepared a negative electrode for a lithium ion battery, and the specific differences from Example 1 are as follows:
[0148] The coating thickness, number of surfaces, and polymer used of the cation conductive polymer layer slurry are different. The specific differences are shown in Table 1.
[0149] Application Examples
[0150] This example provides a lithium-ion battery, specifically:
[0151] The negative electrode is the negative electrode of the lithium ion battery provided in the embodiment or the comparative example.
[0152] The positive electrode is prepared by fully stirring and mixing the positive electrode material lithium cobalt oxide, the conductive agent acetylene black, and the binder polyvinylidene fluoride (PVDF) in an N-methylpyrrolidone solvent system in a mass ratio of 98:1.2:0.8, coating the mixture on an Al foil, and obtaining the positive electrode after drying, rolling, and slitting.
[0153] The diaphragm is a porous polymer film of polyethylene (PE).
[0154] The electrolyte is prepared by mixing lithium salt LiPF6 and non-aqueous organic solvent (ethylene carbonate (EC): diethyl carbonate (DEC): propylene carbonate (PC): propyl propionate (PP): vinylene carbonate (VC)) = 25:25:15:31:4, mass ratio) in a mass ratio of 8:92.
[0155] Lithium-ion battery assembly: The positive electrode, negative electrode and separator are stacked to form a battery cell, and the specific separator is set between the positive electrode and the negative electrode; the battery cell is placed in an aluminum-plastic film, and then the electrolyte is injected into it and packaged to obtain a lithium-ion battery.
[0156] Test Case
[0157] This example tests the thermal stability of the lithium-ion battery obtained in the application example. The specific test method is as follows:
[0158] Preparation process: Place at room temperature (25℃±3℃) for 5 minutes, then discharge at 0.2C constant current to 3.0V and place for 5 minutes; continue to charge at 2C constant current and constant voltage to 4.25V, with a cut-off rate of 1.5C; finally charge at 1.5C constant current and constant voltage to 4.53V, with a cut-off rate of 0.05C; place for 120 minutes and then use for testing.
[0159] Test process: Put the prepared lithium-ion battery into the oven, and heat the oven temperature to the set temperature (124℃, 126℃, 128℃, 130℃, 132℃ or 134℃) at a rate of 5±2℃ / min, and keep it for 60 minutes before stopping. During the test, the surface temperature, ambient temperature and voltage of the lithium-ion battery need to be monitored; if the lithium-ion battery does not catch fire or explode, it is qualified.
[0160] Regarding the thermal stability test, it should be noted that the higher the temperature and the greater the cut-off voltage, the more difficult it is to pass the safety test. If the 4.53V-0.05C-60min-130℃ hot box fails, it means that the 4.53V-0.05C-60min-132℃ hot box will definitely not pass, and there is no need to test again. Therefore, some conditions in Table 1 have no corresponding results.
[0161] The specific test results are shown in Table 1.
[0162] Table 1 Hot box safety performance of lithium-ion batteries obtained in application examples
[0163]
[0164] In Table 1, when double-sided coating is performed, it means that the coating thickness of both sides is the same, and the listed thickness is the total thickness, that is, the single-sided thickness is half of the listed thickness.
[0165] This example also conducted a high temperature external short test of the lithium-ion battery obtained in the application example. The specific process and results are as follows:
[0166] Preparation process: Leave at room temperature (25℃±3℃) for 5 minutes, then discharge at 0.2C constant current to 3.0V and leave for 5 minutes; charge at 0.5C constant current and constant voltage to 4.53V, with a cut-off rate of 0.02C; leave for 120 minutes before use for testing.
[0167] Test process: select several groups from the above embodiments and 10 battery cells from the comparative examples and place them in an environment with a target temperature (53°C, 55°C, 57°C). After the battery surface temperature reaches the target temperature, place it for another 30 minutes, then short-circuit the positive and negative poles of the battery cell with a load of 70±5mΩ resistance, and monitor the surface temperature and voltage of the battery cell. The test terminates when one of the following two situations occurs: a. The battery cell temperature drops to 20% lower than the peak value; b. The short-circuit time reaches 24h.
[0168] Regarding the high temperature short test, it should be noted that the higher the temperature, the greater the resistance, and the more difficult it is to pass the safety test. A test result of 100% is considered to have passed the high temperature short safety test, and other results are considered to have failed. The above test results are shown in Table 2.
[0169] Table 2 High temperature external short safety performance of lithium-ion batteries obtained from some application examples
[0170]
[0171] Keeping the coating surface and coating thickness unchanged, and changing the type of polymer, for example, from Comparative Examples 1, 3, 5 and Examples 5 and 11, it can be seen that among the four polymers used in the specific implementation, the improvement of the safety performance of lithium-ion batteries has the following trend: no coating < Nafion115 < PSF (unmodified polyarylethersulfone) < PSF-SA < PSF-NI. This shows that the increase in the length of the side chain improves the proton conductivity and thermodynamic stability of the cation-conducting polymer layer; further, PSF-NI has better thermal stability and mechanical properties even above 200°C due to the rigid structure of the main chain and the benzenesulfonamide group of the side chain, and has higher ion conductivity; in addition, the lower cost and excellent fuel permeation prevention performance make the modified aromatic polymer a more ideal alternative material for improving the performance of the hot box than the unmodified aromatic polymer Nafion115 or PSF in the related art.
[0172] By comparing the embodiments and comparative examples, it can be seen that when the types of polymers used are the same, the effect of the lithium-ion battery negative electrode containing a double-sided coated cation conductive polymer layer is better than the effect of a single-sided coated cation conductive polymer layer, and better than the effect of a cation conductive polymer layer without any coating.
[0173] Keeping the material of the cation conductive polymer layer unchanged, by comparing the thickness embodiments, it can be seen that: when single-sided coating or double-sided coating is performed and the single layer thickness is between 2.5 and 10 μm (excluding the endpoint value), the hot box temperature (the hot box temperature is the temperature when 100% passes) will be increased. When PSF-NI is coated with 5 μm on both sides, the hot box temperature will be increased by more than 8°C, when PSF-SA is coated with 5 μm on both sides, the hot box temperature will be increased by more than 6°C, PSF will increase the hot box temperature by more than 2°C, and Nafion115 (related technology) will have no effect on the hot box. When the single-sided coating thickness is 10 μm, the ability of the cation conductive polymer to improve the hot box will be affected. Therefore, we speculate that when the single-sided coating thickness is greater than 10 μm, the hot box will be deteriorated and the battery structure and performance will be affected.
[0174] By comparing Table 1 and Table 2, it can be seen that the high-temperature external short performance and hot box safety performance trends of the lithium-ion battery provided by the present invention are similar, both of which have a trend that double-sided coating is better than single-sided coating, and no coating <Nafion115 <PSF (unmodified polyarylethersulfone) <PSF-SA <PSF-NI.
[0175] In summary, the lithium battery negative electrode including the cation conductive polymer layer provided by the present invention can improve the thermal stability of the lithium ion battery to a certain extent, and it has good anti-oxidation stability, thereby preventing the battery failure caused by oxidation of the lithium ion battery negative electrode; it can also be + , ensuring the normal electrochemical reaction in lithium-ion batteries; having excellent thermal stability, improving the high-temperature storage performance of lithium-ion batteries, and increasing the cycle life of lithium-ion batteries at high temperatures. The preparation method of the cation conductive polymer layer is relatively simple and low in cost, and can be directly used in battery production.
[0176] The above is a detailed description of the embodiments of the present invention, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
Claims
1. A negative electrode for a lithium ion battery, characterized in that: The lithium ion battery negative electrode comprises a negative electrode current collector, a negative electrode coating and a cation conductive polymer layer which are stacked; The material of the cation conductive polymer layer is a modified aromatic polymer; The modified aromatic polymer includes at least one of a sulfonamide-modified polymer and a sulfonated side-chain grafted polymer.
2. The lithium ion battery negative electrode according to claim 1, characterized in that: The unmodified aromatic polymer includes at least one of polyaryletherketone, polysulfide sulfone, polyetheretherketone, naphthyridine polyethersulfoneketone, polyimide, polybenzimidazole, polyarylethersulfone, polyarylethersulfone, sulfonated polyphenylene ether and polyphenylene polymers; preferably, the modified aromatic polymer is selected from at least one of sulfonamide-modified polyarylethersulfone and sulfonated side-chain grafted polyarylethersulfone.
3. The lithium ion battery negative electrode according to claim 1, characterized in that: The thickness of the cation conductive polymer layer is 2.5-10 μm.
4. The lithium ion battery negative electrode according to claim 1, characterized in that: The negative electrode of the lithium ion battery is composed of a superimposed cation conductive polymer layer, a negative electrode coating, a negative electrode current collector, a negative electrode coating and a cation conductive polymer layer; preferably, the negative electrode of the lithium ion battery is composed of a superimposed negative electrode coating, a negative electrode current collector, a negative electrode coating and a cation conductive polymer layer.
5. The lithium ion battery negative electrode according to claim 2, characterized in that: The synthesis method of the sulfonamide-modified polyarylethersulfone comprises the following steps: A1. reacting a polyarylethersulfone and a sulfonyl compound to obtain a sulfonylated polyarylethersulfone; A2. The sulfonylated polyarylethersulfone and the amide compound are reacted to obtain a sulfonamide-modified polyarylethersulfone; Preferably, in step A1, the molar ratio of the sulfonyl compound to the poly(arylethersulfone) is 1.2:1 to 1.5:1; Preferably, in step A1, the sulfonyl compound comprises at least one of sulfonic anhydride, p-toluenesulfonyl chloride and chlorosulfonic acid; Preferably, in step A2, the molar ratio of the amide compound to the sulfonated poly(arylethersulfone) is 1:1 to 1.2:1; Preferably, in step A2, the amide compound comprises at least one of ammonia, ethylamine and propylamine.
6. The lithium ion battery negative electrode according to claim 2, characterized in that: The synthesis method of the sulfonated side chain grafted polyarylethersulfone comprises the following steps: D1. reacting the polyarylethersulfone with an acyl chloride compound to obtain an acylated polyarylethersulfone; D2. reacting the acylated polyarylethersulfone and trisodium 8-hydroxy-1,3,6-pyrenetrisulfonate in the presence of an acid binding agent and a catalyst; Preferably, in step D1, the acyl chloride compound includes at least one of chlorobutyryl chloride (CAS: 7623-11-2; or CAS: 4635-59-0), acetyl chloride, benzoyl chloride, butyryl chloride and propionyl chloride; Preferably, in step D1, the molar ratio of the acyl chloride compound to the poly(arylethersulfone) is 1.1:1 to 1.3:1; Preferably, in step D2, the molar ratio of the acylated polyarylethersulfone to trisodium 8-hydroxy-1,3,6-pyrenetrisulfonate is 1.0:1 to 1.2:
1.
7. A method for preparing a negative electrode for a lithium ion battery according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: S1. Providing a cation conductive polymer layer slurry comprising the modified aromatic polymer, and a component in which the negative electrode current collector and the negative electrode coating are stacked; S2. Coating the cation conductive polymer layer slurry on the surface of the component on the negative electrode coating side.
8. A lithium ion battery, characterized in that: The lithium-ion battery comprises a battery cell, wherein the battery cell comprises a positive electrode, a negative electrode and a separator disposed between the positive electrode and the negative electrode; The negative electrode is a lithium ion battery negative electrode as claimed in any one of claims 1 to 6.
9. The lithium-ion battery according to claim 8, characterized in that: The lithium-ion battery further includes an electrolyte, which infiltrates the battery cell; and / or the lithium-ion battery further includes a battery shell, which accommodates the battery cell.
10. Application of the lithium-ion battery according to claim 8 or 9 in the fields of power batteries, energy storage batteries and 3C small household appliances.